2009
DOI: 10.1007/s10549-009-0358-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial NADH-dehydrogenase subunit 3 (ND3) polymorphism (A10398G) and sporadic breast cancer in Poland

Abstract: Mitochondria are subcellular organelles that produce adenosine triphosphate (ATP) through oxidative phosphorylation (OXPHOS). As suggested over 70 years ago by Otto Warburg and recently confirmed with molecular techniques, alterations in respiratory activity and mitochondrial DNA (mtDNA) appear to be common features of malignant cells. Somatic mtDNA mutations have been reported in many types of cancer cells, but very few reports document the prevalence of inherited mitochondrial DNA polymorphisms in cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 43 publications
(50 reference statements)
4
80
3
2
Order By: Relevance
“…Breast nipple aspirate fluid with mtDNA mutations at positions 204, 207 and 16293 has been suggested as an indicative for breast cancer (6) and mtDNA D-loop mutations have been proposed as independent prognostic marker in breast cancer (7). We have shown that individuals who inherited the A10298G polymorphism are at higher risk for developing BC (8). As A10398G is located in the ND3 (NADHd-dehydrogenase subunit 3) we have been interested if any other polymorphisms are abundant in ND genes in the BC cohort.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Breast nipple aspirate fluid with mtDNA mutations at positions 204, 207 and 16293 has been suggested as an indicative for breast cancer (6) and mtDNA D-loop mutations have been proposed as independent prognostic marker in breast cancer (7). We have shown that individuals who inherited the A10298G polymorphism are at higher risk for developing BC (8). As A10398G is located in the ND3 (NADHd-dehydrogenase subunit 3) we have been interested if any other polymorphisms are abundant in ND genes in the BC cohort.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, the missense mutation G5460A affecting the ND2 was reported in pathologically proven Parkinson and Alzheimer's diseases (28). Therefore, it cannot be excluded that mtDNA polymorphisms may result in disturbed protein synthesis, synthesis rate or finally in changed protein structure and therefore influence mitochondrial and cell physiology with the consequence of cancer development susceptibility (3)(4)(5)8,29).…”
Section: Amino Acid Change Gene -------------------------------------mentioning
confidence: 99%
“…Nevertheless, this haplogroup is characterized by many RFLP-markers and no single mtDNA position may serve as a cancer marker. Therefore, it is possible that the interactions of multiple mitochondrial DNA variant modify breast cancer risk in the case of haplogroup I (62), possibly with special role of A10398G polymorphism (35,37). Other haplogroups seem to be represented in the cancer population at a frequency similar to the general Polish population.…”
Section: Haplogroup Distributions Differs Breast Cancer Patientsmentioning
confidence: 99%
“…There is an association between somatic mtDNA mutations and cancer development, progression and metastasis (18,21,(30)(31)(32)(33)(34)(35)(36)(37). In addition, recent studies have shown that inherited polymorphisms or mutations of the mitochondrial genome may modulate the risk of developing cancer, including prostate, oral and colorectal cancers (18,(38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation